Socioeconomic diversity and typology of Bedouin communities in the hot dry Coastal Zone of Western Desert, Egypt - Aboul-Naga, Adel M.; Mogahed, Waheed; Fahmy, Faten; Elshafi, Mohamed; Abdel-Aal, Ehab S.; Abdel-khalek, Tarek; Abdelsabour, Taha H.; Alary, Veronique (Frontiers in Sustainable Food Systems, 2022)
The study was carried out to assess the diversity of farming and the associated development needs of Bedouin communities in the hot dry rural area of Coastal Zone of Western Desert (CZWD), Egypt. The area is hot dry, with low irritated rainfall (60-140 mm/yr.), and frequent incidence of drought. Specially designed questionnaires were adopted on 151 householders and 51 women groups in 4 locations. More than 50% of the householders are fully engaged in agriculture activities, whereas 31% of them are partially engaged in other business. The families are extended average 12.2 members. Gender differences in the education level are recognizable; 20% of males ≥15 years of age are illiterate vs. 60% females. Dominant agriculture activity of the householders are sheep raising (98.7%), goat raising (89.4%), olive and figs cultivation (84%), and rain-fed barley (78%). Land tenure average 31.3 acres/ household. Crop cultivation rely on the rainfall; 29 % apply supplement irrigation for fruit and vegetables. Natural pasture is an important asset for the livestock, where small householders do hold pastureland. Females ≥15 yrs. do not contribute to field cropping, while 53% of them participate to animal husbandry, especially at house. Typology of the studied stakeholders showed clear diversification in farming systems. They are clustered in 4 groups; depending mainly on livestock assets, followed by land/crop and human assets. Number of species and flock size are the most important variables for the diversity of stakeholders Cultivated area is the main variable within land/crop assets, Family members in livestock, and family size are the main variable in human assets. Most of the householders (95%) give their top need for water cisterns. Water reservoirs ranked the second (78.6%), followed by goat raising and improvement. Pasture development got the lowest priority. Goat and poultry rearing, plus dairy processing got top needs by women.